Olivia Goes to the Library - Forte, Lauren; Boutilier, Kate; Casemiro, Eryk (Ready-to-read. Star reader!, 2013)
When Olivia puts down her favorite book during story time at the library, it goes missing! Help Olivia find it in time for her bedtime story.